Optimal Debt Bias in Corporate Income Taxation - Jenny Simon (Center for Economic Studies and ifo Institute (CESifo), 2015)
I present a rationale for a government to discriminate between debt and equity financing when taxing corporate income. For risk-averse entrepreneurs, equity generates more surplus than debt, because it provides financing and insurance. A government seeking to extract surplus from entrepreneurs would naturally tax equity-generated income more than debt-generated income. I also establish a less obvious reason why the government might want to extract surplus from entrepreneurs. It is well understood that when the quality of projects is unobservable to investors, risk-averse entrepreneurs with higher-return projects might retain a larger share of equity to signal their type (Leland and Pyle (1977)). I show that in such an adverse selection set-ting, while competitive investors are constrained to offer actuarially fair terms, the government can use taxes to discriminate between types. This degree of freedom allows manipulation of the relevant incentive constraints so that a lower level of debt suffices for separation, and an increase in overall efficiency can be obtained. Since entrepreneurs separate along their debt-to-equity ratios, the optimal non-linear tax schedule to achieve the desired discrimination is isomorphic to one that taxes debt-generated income at a lower rate than equity-generated income.
Keywords: G18; G11; H25; D82; 330; corporate taxation; debt bias; investment decision under asymmetric information